A novel face of immediate-early genes: transcriptional operations dominated by c-Jun and Jun D proteins in neurons following axotomy and during regenerative efforts - Herdegen, Thomas; Brecht, Stephan; Fiallos-Estrada, Carlos E.; Wickert, Hannes; Gillardon, Frank; Voss, S.; Bravo, Rodrigo; Zimmermann, Manfred (Immediate-early genes in the central nervous system, 1995)
The investigation of immediate-early genes (IEGs) in neurons and glial cells represents a new research area in neurobiology. IEGs are rapidly expressed by transsynaptic stimulation or transmembranous information transfer. A substantial number of IEGs encode for transcription factors (TF) which are involved in the control of gene transcription. The early appearance of TF offers a new access to elucidate the link between intentional stimuli and neuroplastic-reactive responses of neurons via alterations of protein synthesis. The expression of IEG encoded TF can be visualized by immunocytochemistry on the protein level (Herdegen et al. 1991a; Hunt et al. 1987; Kovary and Bravo 1991a,b; Morgan et al. 1987) or by in situ hybridization on the mRNA level (Cole et al. 1989; Wisden et al. 1990).
Gesehen am 18.08.2025